A Rare but Fatal Behçet Variant: The Hughes–Stovin Syndrome—Successful Case Report and New Evidence from Literature Review - Ascoli Marchetti, Andrea; Belvivere, Lorella; Argirò, Renato; Kroegler, Barbara; Oddi, Fabio M.; Pennetta, Federico; Giorgi, Alice de; Fazzini, Stefano; Morosetti, Daniele; Triggianese, Paola; Greco, Elisabetta; D'Antonio, Arianna; Coccia, Ilaria; Tesauro, Manfredi; Sangiuolo, Federica; Ippoliti, Arnaldo (AORTA, 2023)
Hughes–Stovin syndrome (HSS) is a rare potentially fatal vasculitis supposedly belonging to the spectrum of Behçet disease without ocular involvement. HSS tends to play by a temporal pattern, starting with thrombosis and followed by formation of pulmonary aneurysms. Since its mortality can reach 25% of cases, early recognition and appropriate therapy represent the major clinical challenges. We describe a rare case of HSS successfully treated via multidisciplinary management by an endovascular approach and immunosuppressive therapy.
Keywords: Behçet disease; Hughes–Stovin syndrome; pulmonary artery aneurysm; endovascular treatment; genetic syndrome; vena cava filter; deep venous thrombosis; CT scan